2002
DOI: 10.1046/j.1442-2026.2002.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of major chronic iIlnesses and hospital admissions via the emergency department in a randomized older population in Randwick, Australia

Abstract: Objective: To find out if patients with chronic illnesses living in the community are at risk of unplanned hospital admissions through emergency departments; what types of chronic illnesses may be putative risk factors; and if an increase in the number of chronic illnesses may be associated with increased risk. Methods: The survey included the completion of a standardized questionnaire for medical illnesses in a random sample of older people dwelling in the community and analysis of admission records to our ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 13 publications
1
29
0
2
Order By: Relevance
“…Die Inanspruchnahme stationärer Versorgungsleistungen durch ältere multimorbide Patienten wurde größtenteils anhand folgender Endpunkte untersucht: Zahl der Krankenhauseinweisungen [17,20,21,22,23,24,25], der Tage oder Näch-te im Krankenhaus [16,21,22] und der Notaufnahmen [26,27,28,29] innerhalb eines Jahres sowie der ungeplanten Wiedereinweisungen innerhalb eines Monats oder Jahres [30,31,32]. Die gesamte Evidenz entstammt der ausländischen Literatur.…”
Section: Stationäre Versorgungunclassified
See 1 more Smart Citation
“…Die Inanspruchnahme stationärer Versorgungsleistungen durch ältere multimorbide Patienten wurde größtenteils anhand folgender Endpunkte untersucht: Zahl der Krankenhauseinweisungen [17,20,21,22,23,24,25], der Tage oder Näch-te im Krankenhaus [16,21,22] und der Notaufnahmen [26,27,28,29] innerhalb eines Jahres sowie der ungeplanten Wiedereinweisungen innerhalb eines Monats oder Jahres [30,31,32]. Die gesamte Evidenz entstammt der ausländischen Literatur.…”
Section: Stationäre Versorgungunclassified
“…2). In einer ebenfalls mit administrativen Daten durchgeführten schwedischen Studie [23] hatten Patienten mit drei oder mehr Krankenhauseinweisungen signifikant mehr chronische Erkrankungen (3,45) [30,31,32] oder Notaufnahmen im Allgemeinen [26,27,28,29] betrachtet haben, diesbezüglich einen signifikanten positiven Zusammenhang.…”
Section: Stationäre Versorgungunclassified
“…A similar study was carried out in Germany where age and multimorbidities were found to have strong impacts on use of services 25. Unplanned hospital admissions were discussed in relation to comorbidities and the elderly . Upshur et al .…”
Section: Resultsmentioning
confidence: 99%
“…Much of the literature concentrates on multiple chronic conditions and the elderly reflecting health policy concerns. Given the association between multiple conditions and unplanned emergency department, admissions in the elderly such a concern requires addressing. For those who are not elderly but have multiple conditions, unplanned hospital admissions are also an issue.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of sudden deaths in England, it was found that for cases involving myocardial tissue, death was ascribed to ischaemic heart disease in 82.4% of cases [3]. In the elderly, hypertension and ischaemic heart disease have been found to be significant predictors of emergency room admissions [4].…”
Section: Introductionmentioning
confidence: 98%